Entrepreneurship Training as One Effort to Improve the Family Economy - Munawir Nasir; Kirana Ikhtiari; Fyrdha Faradyba Hamzah (Golden Ratio of Community Services and Dedication, 2021)
This community service activity aims to form or develop a community business that is economically independent and helps create jobs and thinking, creative and independent skills for the community. This training activity for making twister chips with potato as an essential ingredient in one of the business product innovations is expected to be a choice for entrepreneurship for Popo Village, Takalar Regency, which is expected to improve their family's economy. The approach method offered to support community service program activities is a participatory method in which partners are directly involved in activities from preparation to implementation. The action is holding meetings in entrepreneurship counseling and training on making twister chips. The type of output produced based on the planned activity in community service is in the form of a modern product with specifications for twister chips with potato as the primary ingredient.